Pharmacy Operationalization of the Intralesional Oncolytic Immunotherapy Talimogene Laherparepvec - McBride, Ali (Hosp Pharm, 2018)
Objective: Oncolytic immunotherapy involves the use of viruses to target and destroy cancer cells and to induce immune responses for an enhanced antitumor effect. Talimogene laherparepvec, a genetically modified herpes simplex virus type 1 (HSV-1) that selectively replicates in tumors to induce lytic cell death, tumor antigen release, and the local production of granulocyte–macrophage colony-stimulating factor (GM-CSF), has been approved for the treatment of a defined population of patients with metastatic melanoma. Talimogene laherparepvec is administered as a series of intralesional injections, and specific procedures are implemented to minimize the risk of viral exposure. Because talimogene laherparepvec represents a novel therapeutic modality, its preparation, administration, and handling requirements differ from current therapies; pharmacists have an important role in developing new procedures to incorporate it into clinical practice. Methods: In this review, pharmacists with experience dispensing talimogene laherparepvec, in the clinical trial setting and/or as a commercially available product at US academic institutions, synthesized their personal experiences through group discussions to provide insights on the ordering, receipt, storage, preparation, administration, and handling of talimogene laherparepvec. Results: Suggestions for patient education and practical guidance to assist hospital pharmacists and decision makers with implementing talimogene laherparepvec at their institutions are provided. Conclusion: These insights may further inform the development of policies or procedures to incorporate talimogene laherparepvec into clinical settings and improve patient outcomes.